2019
DOI: 10.1021/acs.jafc.9b05046
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Major Constituents in Different-Colored Rapeseed Petals by UPLC–HESI-MS/MS

Abstract: Oilseed rape (Brassica napus L.) is the second highest yielding oil crop worldwide. In addition to being used as an edible oil and a feed for livestock, rapeseed has high ornamental value. In this study, we identified and characterized the main floral major constituents, including phenolic acids and flavonoids components, in rapeseed accessions with different-colored petals. A total of 144 constituents were identified using ultrahigh-performance liquid chromatography−HESI-mass spectrometry (UPLC−HESI-MS/MS), 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 48 publications
2
58
3
Order By: Relevance
“…However, the altered flavonoid profile in petals is likely not the cause of color variation in the present study. Previous studies have reported that the yellow color in B. napus flowers is caused by carotenoids pigments (Zhang et al ., 2015) and that the amounts and composition of flavonoids in yellow flowers are not significantly different from those in white flowers (Yin et al ., 2019), indicating that flavonoids do not contribute to the yellow flower pigment in B. napus . In B. rapa , flavonoids accumulate in the basal parts of the yellow petals, and function as a floral UV pigment to attract pollinators (Sasaki and Takahashi, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the altered flavonoid profile in petals is likely not the cause of color variation in the present study. Previous studies have reported that the yellow color in B. napus flowers is caused by carotenoids pigments (Zhang et al ., 2015) and that the amounts and composition of flavonoids in yellow flowers are not significantly different from those in white flowers (Yin et al ., 2019), indicating that flavonoids do not contribute to the yellow flower pigment in B. napus . In B. rapa , flavonoids accumulate in the basal parts of the yellow petals, and function as a floral UV pigment to attract pollinators (Sasaki and Takahashi, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The insertion of a transposable element in BnaC3.CCD4 , the product of which degrades carotenoids into colorless compounds, leads to disruption of BnaC3.CCD4 and a subsequent enhanced accumulation of carotenoids; thus, changing the flower color from white to yellow (Zhang et al ., 2015). Few studies have reported B. napus with other flower colors, and the underlying molecular basis is not well understood (Yin et al ., 2019). Cloning and functional characterization of carotenoid biosynthesis‐related genes in B. napus are important for gaining insight into the mechanism underlying flower coloration, as well as for breeding varieties with different flower colors.…”
Section: Introductionmentioning
confidence: 99%
“…PAs are the most numerous and widely distributed polyphenols in plants and determine seed coat color in Arabidopsis thaliana [9][10][11], Medicago truncatula [19,20], sheepgrass (Leymus chinensis) [21], and B. napus [13,16,22]. In addition, advances in metabolomics technologies have led to numerous flavonoids being identified in B. oleracea [23], B. rapa [24], B. napus [14,25], and B. juncea [26,27]. However, the pathway of flavonoid biosynthesis has been well studied by the TT (TRANSPARENT TESTA) loci in model plant A. thaliana [18,[28][29][30][31][32][33][34], providing valuable resources and references for elucidating the mechanism of seed coat color.…”
Section: Introductionmentioning
confidence: 99%
“…Engineering and breeding of flavonol content is of agronomical, economical, and ornamental importance (Takahashi et al, 2007;Cook et al, 2013;Yin et al, 2019). Besides the potential of engineering flavonol biosynthesis, anthocyanin and proanthocyanindin production can be engineered as FLS and DFR compete for substrates (Figure 8), thereby influencing important agronomical traits e.g.…”
Section: Future Perspectives In Engineering Flavonol Content In B Napusmentioning
confidence: 99%